Dynamics and environmental state of vegetable coverage and land use in landscape regions of the southwestern portion of the Brazilian State of mato grosso - da Silva Neves, Sandra Mara Alves; Kreitlow, Jesã Pereira; da Silva Miranda, Miriam Raquel; dos Santos Galvanin, Edinéia Aparecida [UNESP]; da Silva, João dos Santos Vila; Cruz, Carla Bernadete Madureira; Vicens, Raúl Sánches (My University, 2019)
The objective of this article is to investigate the space-time dynamics of vegetation cover and land use and the Environmental State of the landscape regions of the southwestern portion of the Brazilian state of Mato Grosso.The vegetation cover and land use maps were generated from the Landsat 5 satellite images from 1984, and Landsat 8 from 2013 in the SPRING software. Map quantifications and layouts were elaborated withArcGis. The regionalization and analysis of the environmental state of the landscape were made through a regional geoecological matrix. From the results obtained, it was verified that the anthropic uses in the period of study were expanded by 134.08% while the vegetal coverings were reduced by 21.66% and the water bodies by 39%. Pasture is the predominant land use in the region, 24.09% (31,335.86 km2), mainly occupying the flat and smooth wavy terrain. Forest cover totaled 66.36% (84,967.12 km2), being found mainly in forest fragments, in which the larger territorial dimensions are either protected by environmental legislation or located in indigenous lands. Eight landscape regions were delimited in the southwest portion of Mato Grosso, including the Paraguay River Depression, which presents the landscape with the highest percentage of anthropic uses, predominantly the Degraded Environmental State. It was concluded that there is a need to adopt land use practices that minimize the environmental degradation of landscape regions, considering that during the period under investigation, the expansion of anthropic uses, mainly Livestock, directly influenced the suppression of vegetation cover.
Dinâmica e estado ambiental da cobertura vegetal e dos usos da terra nas regiões de paisagem da porção sudoeste mato-grossense Brasileira
Keywords: Brazilian Cerrado; Geotechnologies; Pantanal; Remote Sensing; Upper Paraguay River Basin